2009
DOI: 10.1016/j.jallcom.2008.08.088
|View full text |Cite
|
Sign up to set email alerts
|

Destruction, amorphization and reactivity of nano-BN under ball milling

Abstract: a b s t r a c tThe processes of mechanical activation of a hexagonal boron nitride (h-BN) and its reactivity upon interaction with hydrogen and water were investigated using X-ray, TEM, Microdiffraction, Dynamic Light Scattering, FTIR-spectroscopy, adsorption (BET). Initial h-BN samples were monocrystalline plates 70-80 nm thick. Mechanical treatment of h-BN is accompanied by plate splitting and formation of crystallographically oriented "rods." The rod thickness gradually diminishes to less than 5 nm. Specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…With the increase of the BN content from 0 to 40 wt % (0 means pure PA12), the corresponding particle size shifts toward the low‐particle‐size direction (from pure PA12 28‐400 μm to PA12/BN [40 wt %] 10‐260 μm), indicating that the incorporation of BN filler particles is beneficial to the reduction in particle size of polymer PA12. Consequently, the rigid h‐BN particles incorporated show the significant effect of grinding‐aid agent on the pulverization of PA12 by effectively cutting the flexible PA12 particles like a sharp blade . Besides, Figure (b) shows the particle size distribution of PA12/BN (40 wt %) system.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…With the increase of the BN content from 0 to 40 wt % (0 means pure PA12), the corresponding particle size shifts toward the low‐particle‐size direction (from pure PA12 28‐400 μm to PA12/BN [40 wt %] 10‐260 μm), indicating that the incorporation of BN filler particles is beneficial to the reduction in particle size of polymer PA12. Consequently, the rigid h‐BN particles incorporated show the significant effect of grinding‐aid agent on the pulverization of PA12 by effectively cutting the flexible PA12 particles like a sharp blade . Besides, Figure (b) shows the particle size distribution of PA12/BN (40 wt %) system.…”
Section: Resultsmentioning
confidence: 98%
“…Consequently, the rigid h-BN particles incorporated show the significant effect of grinding-aid agent on the pulverization of PA12 by effectively cutting the flexible PA12 particles like a sharp blade. 31,32 Besides, Figure 3(b) shows the particle size distribution of PA12/BN (40 wt %) system. Obviously, it can be seen that the size of PA12/BN (40 wt %) copowder prepared via S 3 MCP method ranges from 10 to 260 μm.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the high interest in the possibilities of using mechanically activated BN and its mixtures, the regu larities of the mechanical activation of boron nitride and its reactivity have been poorly studied. The data on the mechanical activation of h BN were first obtained in [5,9,[16][17][18][19]. It was shown that the sizes of CSR decreased, the interlayer distance d(002) increased, and various defects arose in the material.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the sizes of CSR decreased, the interlayer distance d(002) increased, and various defects arose in the material. A question remains being debatable whether the amor phous state is reached during the mechanical activa tion of h BN [5,19] or the defective structure is con fined to a nanocrystalline state [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation